2017
DOI: 10.1103/physrevlett.118.054502
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Grain Mixing Suppresses Droplet Spreading and Splashing during Impact

Abstract: Would a raindrop impacting on a coarse beach behave differently from that impacting on a desert of fine sand? We study this question by a series of model experiments, where the packing density of the granular target, the wettability of individual grains, the grain size, the impacting liquid, and the impact speed are varied. We find that by increasing the grain size and/or the wettability of individual grains the maximum droplet spreading undergoes a transition from a capillary regime towards a viscous regime, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…These two curvatures determine the post-impact dynamics. According to the corresponding crater dimensions (Zhao et al 2015b(Zhao et al , 2017; de Jong, Zhao & van der Meer 2017), the circumference curvature is always larger than the central one. Nevertheless, their relative significance can be altered by the degree of mixing between liquid and grains during the impact.…”
Section: Mixing Ratiomentioning
confidence: 99%
See 3 more Smart Citations
“…These two curvatures determine the post-impact dynamics. According to the corresponding crater dimensions (Zhao et al 2015b(Zhao et al , 2017; de Jong, Zhao & van der Meer 2017), the circumference curvature is always larger than the central one. Nevertheless, their relative significance can be altered by the degree of mixing between liquid and grains during the impact.…”
Section: Mixing Ratiomentioning
confidence: 99%
“…In Formation of a hidden cavity 65 fact, this is consistent with a transition of the droplet spreading dynamics. It has been shown that the viscous dissipation of liquid penetrating into the granular target becomes the largest energy sink in this regime (Zhao et al 2017). Hence, regime c may also be interpreted from an energy perspective: no further dynamics would happen after the impact energy is largely dissipated by the viscosity of the liquid moving in the pores between the grains.…”
Section: Mixing Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies focusing on the dynamic contact angle on rough substrates found that the maximum spreading diameter depends on the Weber number and the contact angle at maximum spreading 21 . Roughness affects the spreading of droplets on hydrophilic grains 22 , but has a minor effect on the spreading of water drops impacting hydrophobic grains 22 . Moreover, Bayer and Megaridis in 2006 found that the slip length, i.e.…”
Section: Introductionmentioning
confidence: 99%